Arabidopsis EXTRA‐LARGE G PROTEIN 1 (XLG1) functions together with XLG2 and XLG3 in PAMP‐triggered MAPK activation and immunity. Issue 3 (31st December 2022) - Wang, Yiping; Zhang, Hailei; Wang, Pengxi; Zhong, Huan; Liu, Wuzhen; Zhang, Shoudong; Xiong, Liming; Wu, Yingying; Xia, Yiji
Abstract: Pattern‐triggered immunity (PTI) is an essential strategy used by plants to deploy broad‐spectrum resistance against pathogen attacks. Heterotrimeric G proteins have been reported to contribute to PTI. Of the three non‐canonical EXTRA‐LARGE G PROTEINs (XLGs) in Arabidopsis thaliana, XLG2 and XLG3 were shown to positively regulate immunity, but XLG1 was not considered to function in defense, based on the analysis of a weak xlg1 allele. In this study, we characterized the xlg1 xlg2 xlg3 triple knockout mutants generated from an xlg1 knockout allele. The strong xlg1 xlg2 xlg3 triple mutants compromised pathogen‐associated molecular pattern (PAMP)‐triggered activation of mitogen‐activated protein kinases (MAPKs) and resistance to pathogen infection. The three XLGs interacted with MAPK cascade proteins involved in defense signaling, including the MAPK kinase kinases MAPKKK3 and MAPKKK5, the MAPK kinases MKK4 and MKK5, and the MAPKs MPK3 and MPK6. Expressing a constitutively active form of MKK4 restored MAPK activation and partially recovered the compromised disease resistance seen in the strong xlg1 xlg2 xlg3 triple mutant. Furthermore, mutations of all three XLG s largely restored the phenotype of the autoimmunity mutant bak1‐interacting receptor‐like kinase 1 . Our study reveals that all three XLGs function redundantly in PAMP‐triggered MAPK activation and plant immunity. Abstract : Arabidopsis EXTRA‐LARGE G PROTEIN 1 (XLG1), like XLG2 and XLG3, positively regulates disease resistance. These XLG proteins are essential for pathogen‐associated molecular pattern‐triggered MAPK activation by interacting with components of the MAPKKK3/5‐MKK4/5‐MPK3/6 pathway to fully activate plant immunity.